Characterization of Gelam Wood Pellets: Effects of Compaction Pressure and Binder Type - Andy Nugraha; Aqli Mursadin; Apip Amrullah; Herry Irawansyah; Randica Erwin M. Tampubolon; Azie Aprianto (International Journal of Marine Engineering Innovation and Research, 2026)
Wood pellets represent a mechanical densification technology that enhances biomass density for more efficient utilization. In this study, Gelam wood was used as the raw material, with variations in binder type (palm sugar and molasses) and compaction pressure (40, 60, and 80 kg/cm²). An experimental approach was employed to directly evaluate the physical and combustion characteristics of the produced pellets. The results indicate that pellets without binder (C3) exhibit superior physical properties, particularly lower moisture and ash content. In contrast, pellets with binders—molasses (C1) and palm sugar (C2)—demonstrate higher calorific values that meet standard requirements. The increased volatile matter observed in C3 suggests a faster ignition and more reactive combustion behavior. Furthermore, combustion characteristics reveal that ignition time, ignition point, and combustion temperature increase proportionally with higher compaction pressure, while the combustion rate shows an inverse trend. Among the tested binders, molasses provides the most favorable combustion performance. Overall, pellets with higher density tend to produce shorter but more stable flames, indicating improved combustion stability. These findings highlight the significant role of compaction pressure and binder type in optimizing the quality and performance of Gelam wood pellets for energy applications.